Recurrent juvenile fibroadenoma of the breast in an adolescent: A case report. Issue 20 (May 2018) - Huang, I-Ching; Li, Pei-Chen; Ding, Dah-Ching
Abstract: Rationale: Most breast masses are benign and are rare in adolescent girls. The most frequent tumor is fibroadenoma. Juvenile fibroadenoma is a rare variant of fibroadenoma and is characterized by rapidly enlarging, painless, and unilateral masses occurring at ages between 10 and 18 years. Patient concerns: A 17-year-old girl who first presented to a hospital due to a left breast tumor. Diagnoses: Juvenile fibroadenoma of the left breast. Interventions: She underwent fibroadenoma excision, but she complained of a mass that presented in her left breast 3 months after surgery. After 2 years of observation, the mass became tender and enlarged. We conducted a wide excision of the tumor. Recurrent juvenile fibroadenoma with hypercellular fibromyxoid stroma of the breast was noted. Outcomes: The patient is in good general condition without tumor relapses during the 4 months of follow-up. Lessons: Recurrent fibroadenomas, particularly those of a large size with a rapid growth rate, in the same breast suggest a high possibility of transformation. We recommend wide tumor resection.